Odpowiedź:
[tex]1)\\\\\frac{2}{5}x-\frac{1}{3}=\frac{1}{5}-\frac{2}{3}x+3\ \ /*15\\\\6x-5=3-10x+45\\\\6x-5=48-10x\\\\6x+10x=48+5\\\\16x=53\ \ /:16\\\\x=\frac{53}{16}\\\\x=3\frac{5}{16}\\\\\\2)\\\\\frac{1}{4}-\frac{2}{3}x=-\frac{1}{3}x+\frac{1}{2}-1\ \ /*12\\\\3-8x=-4x+6-12\\\\3-8x=-4x-6\\\\-8x+4x=-6-3\\\\-4x=-9\ \ /:(-4)\\\\x=\frac{9}{4}\\\\x=2\frac{1}{4}[/tex]
[tex]3)\\\\\frac{2x-5}{3}-2=\frac{1}{3}+3x\ \ /*3\\\\2x-5-6=1+9x\\\\2x-11=1+9x\\\\2x-9x=1+11\\\\-7x=12\ \ /:(-7)\\\\x=-\frac{12}{7}\\\\x=-1\frac{5}{7}\\\\\\4)\\\\\frac{4x-7}{6}-\frac{1}{2}x=\frac{2}{3}-4x\ \ /*6\\\\4x-7-3x=4-24x\\\\x-7=4-24x\\\\x+24x=4+7\\\\25x=11\ \ /:25\\\\x=\frac{11}{25}[/tex]